Cloning and sequencing of a full length cDNA coding for human retinol-binding protein. - Colantuoni, V (1983)
We have isolated and sequenced a cDNA clone coding for human Retinol Binding Protein. The sequence indicates that Retinol Binding Protein is synthesized as a single polypeptide chain precursor which is then matured to the secreted protein by removal of a leader peptide. Southern and Northern blot analysis suggest that the gene is present in one or few copies per haploid genome and is transcribed in a single mRNA species.